1985
DOI: 10.1172/jci111664
|View full text |Cite
|
Sign up to set email alerts
|

Variability in purified dysfunctional C1(-)-inhibitor proteins from patients with hereditary angioneurotic edema. Functional and analytical gel studies.

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 24 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…as selective a loss of activity as did the mutant in this kindred (23,24). The best evidence that this mutation affects only target protease specificity and not the inhibitory mechanism is that, although it has lost activity against Clr, it has acquired inhibitory activity against trypsin (Fig.…”
Section: Methodsmentioning
confidence: 58%
“…as selective a loss of activity as did the mutant in this kindred (23,24). The best evidence that this mutation affects only target protease specificity and not the inhibitory mechanism is that, although it has lost activity against Clr, it has acquired inhibitory activity against trypsin (Fig.…”
Section: Methodsmentioning
confidence: 58%
“…Heterogeneity of the dysmorphic proteins has been demonstrated among different type-II HANE families (5). Studies ofin vitro cell cultures have shown that monocytes from patients with HANE synthesize -50% of normal CI-Inh compared with cells from normal subjects (6), which is in agreement with the autosomal dominant inheritance of the disorder (7).…”
Section: Introductionmentioning
confidence: 63%
“…Genetic analysis of HANE indicates that the molecular genetic defects responsible for Cl INH deficiency are heterogeneous, as are those responsible for many other genetic diseases (1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Analysis of mutant proteins from type II HANE patients provided the first evidence for genetic heterogeneity: the proteins from different families differ in electrophoretic mobility, size, and function (6,15,16). Evaluation of the Cl INH gene by Southern blot analysis in both types of HANE has revealed RFLP in -10-15% of kindred (10).…”
Section: Introductionmentioning
confidence: 99%